2009
DOI: 10.1007/978-3-642-04268-3_123
|View full text |Cite
|
Sign up to set email alerts
|

Using Real-Time fMRI to Control a Dynamical System by Brain Activity Classification

Abstract: Abstract. We present a method for controlling a dynamical system using real-time fMRI. The objective for the subject in the MR scanner is to balance an inverted pendulum by activating the left or right hand or resting. The brain activity is classified each second by a neural network and the classification is sent to a pendulum simulator to change the force applied to the pendulum. The state of the inverted pendulum is shown to the subject in a pair of VR goggles. The subject was able to balance the inverted pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…We have demonstrated that it is possible to control a dynamical system [32] and communicate [33] by classifying the brain activity every second; similar work has been done by LaConte et al [34]. deCharms et al [35] helped subjects to suppress their pain by letting them see their own brain activity in real-time.…”
Section: More Advanced Real-time Analysissupporting
confidence: 54%
“…We have demonstrated that it is possible to control a dynamical system [32] and communicate [33] by classifying the brain activity every second; similar work has been done by LaConte et al [34]. deCharms et al [35] helped subjects to suppress their pain by letting them see their own brain activity in real-time.…”
Section: More Advanced Real-time Analysissupporting
confidence: 54%
“…Although our reported real-time system used an SVM implementation (Joachims, 1999), this is really a modular part of the system that allows future extensions in which multiple classifiers (either individually or combined) can be used (LaConte et al, 2007). Recently Eklund et al (2009) 4. An example AFNI rtfMRI display with stimulus window.…”
Section: Resourcesmentioning
confidence: 98%
“…Using this system, Papageorgiou et al (2009) has recently reported the ability to provide feedback based on slow vs. fast inner, automatic speech. Using a similar approach based on neural networks, Eklund et al (2009) has reported the ability to control the dynamics of a simulated inverted pendulum, using classification of left, right, and resting conditions. Using the relevance vector machine, Hollmann et al (2009) presented a subject's neuroeconomic decisions to the operator before that subject pressed a button to convey his decision.…”
Section: Introductionmentioning
confidence: 98%
“…While previous fMRI based BCI have classified between two classes [1] or three classes [2], we instead classify between five different classes, to give the subject five degrees of freedom. We choose to use our system for communication, since EEG has been used for communication [3] and many have claimed that fMRI is far too slow for similar setups.…”
Section: Introductionmentioning
confidence: 99%